Magbox Games to Improve Literacy of Grade VI Elementary School Students on Short Story Materials - Anggela, Anggun Fitri Puji; Setiawan, Dwi Agus; Rahutami, Rahutami (Universitas Pendidikan Ganesha, 2025)
Students’ literacy levels in Indonesia remain relatively low, indicating the need for innovative instructional approaches that can enhance engagement and interest in literacy. The solution that can be offered is to use learning media that is integrated with the game. This study aims to develop an educational game-based learning media called Magbox Games, equipped with a teacher’s guidebook and short story materials. The development followed the ADDIE model, which consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. The validity test involved three expert validators media, content, and language experts along with one teacher as a practitioner and 16 students as participants. Data collection was conducted through expert validation questionnaires and student response questionnaires. The results of the development show that Magbox is both feasible and practical, based on validation results and classroom trials. The feasibility test revealed that the media expert gave a score of 96%, the content expert 82%, and the language expert 96%. The practicality test showed that the teacher gave a score of 96.8%, while student responses were 80% in small groups and 93.7% in large groups. This research is expected to contribute to the development of interactive learning media and improve literacy skills among elementary school students.